A novel printed antenna for ultrawideband RFID (UWB-RFID) tag - Abdel-Raouf, Hany Essam Eldin; Obsiye, Abdi K.H.; Islam, Md. Rafiqul (John Wiley, 2010)
In this article, we present the design of a modified crescent antenna for ultrawideband (UWB) radio frequency identification (RFID) tag. Different studies to optimize the design of this antenna for the UWB-RFID system have been performed, particularly to overcome the main challenges such as minimizing the size of the antenna, improving its read range, and the effects of the metallic objects on the antenna performance. To avoid the effect of the metals that may exist below the partial ground plane, the antenna is designed using a foam layer below the partial ground plane and a full ground plane below the foam layer at the bottom of the structure. As a result, the proposed antenna has a maximum read range between 0.9 m and 4.4 m, with the ability to cover the UWB with the existing of metallic objects below the antenna.